ADVERSE EVENTS RELATED TO DRUG ADMINISTRATION BY THE NURSING TEAM: : AN INTEGRATIVE REVIEW - Rodrigues Vaz, Aline; Sousa De Oliveira, Daniely; Vilanova Araújo, Raquel; Norberta Mendes, Polyana; Átila Pereira de Araújo, Carlos; Raquel Sousa Fernandes, Catiane; Machado Miranda Leal Barbosa, Sara (Health and Society, 2021)
Medications are key resources used to alleviate patient suffering, but they carry the inherent risk of causing adverse events. Method: this is an integrative review using the terms: nursing, medication, adverse drug events, medication administration and patients. Data were categorized in Excel and categorized according to the research question. Results: Among the types of adverse events found, nausea and vomiting prevailed (n= 5; 24%); hypotension (n=4; 17%); Tachycardia and drowsiness (n=3; 14%); allergic reaction (n=2; 10%), headache and hypoglycemia (n=1; 5%).Conclusion: ADE had a direct impact on the increase in the length of hospital stay, deaths and secondary damage to the patient's health, and indirectly on the increase costs of hospitalizations.